Group intervention with parents of adolescents with internalizing behavior problems (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Adolescent behavior problems consist of an important study focus for Psychology and the evaluation of interventions is necessary. The objective of this study was to report the effects of the Promove-Pais, in a group, with parents of adolescents with internalizing behavior problems. The participants were three parents (a couple and a mother) of two adolescents with internalizing behavior problems. The evaluation tests were the REHSE-P, CBCL, PHQ-9 and the Semi-Structured Script Clinical Interview. In total there were 10 sessions lasting an hour and a half each. Comparing the data obtained in the pre-test to the post-test and follow-up, it was noted that parents learned new educational practices and their adolescents no longer had internalizing problems. Thus, there was an improvement in the social interactions of these parents with their children and vice-versa, demonstrating the effectiveness of this the intervention.
Keywords: parent group; parenting social skills; internalizing behavior problems; parenting practices; Promove-Pais